Impact of DNA Extraction Method on Variation in Human and Built Environment Microbial Community and Functional Profiles Assessed by Shotgun Metagenomics Sequencing - Sui, Hui-yu; Weil, Ana A.; Nuwagira, Edwin; Qadri, Firdausi; Ryan, Edward T.; Mezzari, Melissa P.; Phipatanakul, Wanda; Lai, Peggy S. (Frontiers in Microbiology, 2020)
Both the host microbiome and the microbiome of the built environment can have profound influences on human health. While prior studies have suggested that the variability introduced by DNA extraction method is less than typical biologic variation, most studies have focused on 16S rRNA amplicon sequencing or on high biomass fecal samples. Shotgun metagenomic sequencing provides advantages over amplicon sequencing for surveying the microbiome but is a challenge to perform in lower microbial biomass samples with high human DNA content such as sputum or vacuumed dust. Here we systematically evaluate the impact of four different extraction methods (phenol:choloroform, and three high-throughput kit-based approaches including the Promega Maxwell gDNA, Qiagen MagAttract PowerSoil DNA , and ZymoBIOMICS 96 MagBead) on resulting variation in microbial community structure and predicted microbial function assessed by shotgun metagenomics sequencing in human stool, sputum, and vacuumed dust obtained from ongoing cohort studies or clinical trials. We used the same beadbeating protocol for all samples in order to focus our comparison on the impact of kit chemistries. DNA yield was overall highest in the phenol:choloroform and Promega approaches. Only the phenol:choloroform approach showed evidence of contamination in negative controls. Bias based on use of mock community controls was noted across all extraction methods, although Promega exhibited the least amount of bias. The extraction method did not impact the proportion of human reads, although stool had the lowest proportion of human reads (0.1%) as compared to dust (44.1%) and sputum (80%). The impact of extraction method on microbial community structure differed by sample type with extraction method having the least impact in stool and the most impact in vacuumed dust (PERMANOVA R2 0.03, p = 0.001 for stool; R2 0.12, p = 0.001 for sputum; R2 0.13 p = 0.007 for vacuumed dust). Similar differences were noted when evaluating microbial community function. Our results will inform investigators planning microbiome studies using diverse sample types in large clinical studies. A consistent DNA extraction approach across all sample types is recommended, particularly with lower microbial biomass samples that are more heavily influenced by extraction method.